Frontal cortical mitochondrial dysfunction and mitochondria-related β-amyloid accumulation by chronic sleep restriction in mice. Issue 12 (17th August 2016) - Zhao, Hongyi; Wu, Huijuan; He, Jialin; Zhuang, Jianhua; Liu, Zhenyu; Yang, Yang; Huang, Liuqing; Zhao, Zhongxin
Abstract : Mitochondrial dysfunction induced by mitochondria-related β-amyloid (Aβ) accumulation is increasingly being considered a novel risk factor for sporadic Alzheimer's disease pathophysiology. The close relationship between chronic sleep restriction (CSR) and cortical Aβ elevation was confirmed recently. By assessing frontal cortical mitochondrial function (electron microscopy manifestation, cytochrome C oxidase concentration, ATP level, and mitochondrial membrane potential) and the levels of mitochondria-related Aβ in 9-month-old adult male C57BL/6J mice subjected to CSR and as an environmental control (CO) group, we aimed to evaluate the association of CSR with mitochondrial dysfunction and mitochondria-related Aβ accumulation. In this study, frontal cortical mitochondrial dysfunction was significantly more severe in CSR mice compared with CO animals. Furthermore, CSR mice showed higher mitochondria-associated Aβ, total Aβ, and mitochondria-related β-amyloid protein precursor (AβPP) levels compared with CO mice. In the CSR model, mouse frontal cortical mitochondrial dysfunction was correlated with mitochondria-associated Aβ and mitochondria-related AβPP levels. However, frontal cortical mitochondria-associated Aβ levels showed no significant association with cortical total Aβ and mitochondrial AβPP concentrations. These findings indicated that CSR-induced frontal cortical mitochondrial dysfunction and mitochondria-related Aβ accumulation, which was closely related to mitochondrial dysfunction under CSR.